Preoperative sonographic assessment of a leiomyoma of the round ligament: Leiomyoma of the round ligament - Arezzo, Francesca; Cazzato, Gerardo; Loizzi, Vera; Cataldo, Viviana; Mongelli, Michele; Lombardi, Claudio; Cormio, Gennaro (Acta Biomedica Atenei Parmensis, 2022)
NA